Reclamation of a limestone quarry: effect of poultry manure and humic acid on the soil improvement - Tedi Yunanto; Suparno Suparno; Farisatul Amanah; Firdha Fajriatunnisa; Nabila Putri Wisnu (Brawijaya University, 2022)
Limestone processing produces dust covering the soil around the quarry site and may affect soil fertility. Post-mining activities in a forest area are mandatory to restore biodiversity, such as tree species of non-wood products. This study aimed to determine the impact of limestone dust on soil and measure the effectiveness of soil treatment for revegetation. This study employed a randomized block design with three soil groups, i.e. uncovered with limestone dust, covered with 2.5 cm limestone dust, and covered with 5 cm limestone dust. Each group had five replications and was treated with poultry manure (0 kg m-2, 5 kg m-2, 10 kg m-2, and 15 kg m-2) and 2 L of 1% (v/v) humic acid. The amendment of manure and humic acid increased the soil organic C, total N, C/N ratio, and exchangeable K but increased the soil available P content. The soil respiration and total bacteria increased along with the thinning of the limestone dust. Overall, the treatments significantly affected pH, C/N ratio, exchangeable K, and electrical conductivity. At the same time, the group significantly affected organic C, total N, C/N ratio, exchangeable K, electrical conductivity, cation exchange capacity, bulk density, total bacteria, and clay. Based on land suitability assessment guidelines, the soil required nutrient improvement and pH reduction to grow proper non-wood products tree species.